Hierarchical S-modified Cu porous nanoflakes for efficient CO2 electroreduction to formate. Issue 37 (12th September 2022) - Liu, Li-Xia; Li, Xiang; Cai, Yanming; Du, Huitong; Liu, Fuqiang; Zhang, Jian-Rong; Fu, Jiaju; Zhu, Wenlei
Abstract : Hierarchical S-modified Cu porous nanoflakes with abundant active sites, fast charge transfer, and high active edge sites were designed as electrocatalysts for CO2 conversion to formate with ultra-high current (404.1 mA cm −2 ) density and FE (89.8%). Abstract : Electrochemical reduction of CO2 into liquid fuels is a promising approach to achieving a carbon-neutral energy cycle but remains a great challenge due to the lack of efficient catalysts. Here, the hierarchical architectures assembled by ultrathin and porous S-modified Cu nanoflakes (Cu–S NFs) are designed and constructed as an efficient electrocatalyst for CO2 conversion to formate with high partial current density. Specifically, when integrated into a gas diffusion electrode in a flow cell, Cu–S NFs are capable of delivering the ultrahigh formate current density up to 404.1 mA cm −2 with a selectivity of 89.8%. Electrochemical tests and theoretical calculations indicate that the superior performance of the designed catalysts may be attributed to the unique structure, which can provide abundant active sites, fast charge transfer, and highly active edge sites.